Recycling of CDW and Steel Slag in Drainage Layers of Transport Infrastructures. (2016) - Roque, A.J.; da Silva, P.F.; Rodrigues, G.; Almeida, R.
Abstract: Using waste as a civil engineering construction material represents an important environmental and economic advantage. In this context, it was studied the durability and permeability of a crushed concrete recycled aggregate (CCCDW ), processed from construction and demolition waste (CDW), and an inert steel aggregate for construction (ISAC), processed from electric arc furnace (EAF) steel slag, with the aim to evaluate the technical feasibility of their recycling in the drainage layers of transport infrastructures. The durability of recycled materials was studied using the slake-durability test (SDT) proposed by International Society for Rock Mechanics (ISRM). In order to test the behaviour of the material in mechanical conditions more adverse than those specified in the ISRM method, more 600 rotation cycles than those foreseen in the original method were applied. As a complement to SDT tests, macro- and micropetrographic observations as well as physical characterizations of two recycled materials, both before and after SDT tests, were performed. Regarding the hydraulic behaviour of the recycled materials, constant-head permeability tests were carried out on specimens prepared from grain-size fractions in the ranges 0.25-2.0 mm and 2.0-20.0 mm. In the study was compared the behaviour of two recycled materials with two reference natural materials, a basalt and a limestone. The results obtained show, for the conditions tested, the technical feasibility of their recycling in the mentioned applications.